2015
DOI: 10.1371/journal.pone.0119516
|View full text |Cite
|
Sign up to set email alerts
|

The Teratogenicity and the Action Mechanism of Gallic Acid Relating with Brain and Cervical Muscles

Abstract: Gallic acid (3,4,5-trihydroxybenzoic acid) (GA) and other flavanoids are extensively used in nutraceuticals because of their antioxidant and antiinflammatory properties. While examining whether GA is effective in alleviating valproic-acid-induced teratogenesis in a chicken embryo model (CEM), we observed embryo hemorrhage and liposis in the musculi longissimus cervicis. We conducted this study to determine whether GA is inherently teratogenic and the extent to which the risk can be transferred to fetuses. A CE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
(86 reference statements)
0
6
0
Order By: Relevance
“…Besides, new GA features, such as inhibition of aldose reductase, have been reported [ 21 ]. Although GA is believed to have a low risk of side effects, doses greater than 1.02 mg/kg might have teratogenic properties and pose a threat to the fetus in pregnant women [ 22 ]. So, choosing the best concentration and dose for GA is an essential concern in the studies.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, new GA features, such as inhibition of aldose reductase, have been reported [ 21 ]. Although GA is believed to have a low risk of side effects, doses greater than 1.02 mg/kg might have teratogenic properties and pose a threat to the fetus in pregnant women [ 22 ]. So, choosing the best concentration and dose for GA is an essential concern in the studies.…”
Section: Introductionmentioning
confidence: 99%
“…The present study showed that prenatal administration of the high dose of green coffee induced hemorrhage in the cerebral cortex, cerebellum, and spinal cord of the developing rat fetuses. Gallic acid has been reported to be teratogenic at early embryonic development and induced severe cerebral hemorrhage in E9.5 embryos in a dose-dependent manner (Hsieh et al 2015). This cerebral hemorrhage was attributed, partly, to the strong prooxidant nature of gallic acid (Lee et al, 2005;Eslami et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that a small concentration of gallic acid, about 1.02 mg/kg or more, can induce teratogenicity and result in cerebral hemorrhage. This concentration of gallic acid could be easily consumed in tea or coffee, imposing risk to the developing fetus (Hsieh et al 2015). In addition to gallic acid, other polyphenols, present in the coffee extract, are considered to be ROS releasing compounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gallic acid, both natural and synthetic analogue having protocatechuic acid alkyl esters, inhibits HIV -1 protease 17 . The pro-oxidant and auto-oxidative behaviours of gallic acid have also been reported [18][19] .…”
Section: Introductionmentioning
confidence: 86%